2011
DOI: 10.1111/j.1365-2222.2011.03891.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and diversity of allergic rhinitis in regions of the world beyond Europe and North America

Abstract: Our findings suggest that the greater diversity in prevalence of AR or AR/C in populations in these regions is in contrast to the lower diversity of AR or AR/C in the 'western populations (USA and Europe), which tend to be more uniform. This review provides a comprehensive database of the important allergens and triggers which are likely to influence the prevalence of allergic rhinitis in these diverse regions, where the prevalence of allergic rhinitis is increasing and its adverse impact on the quality of lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
135
3
8

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(151 citation statements)
references
References 134 publications
5
135
3
8
Order By: Relevance
“…1 Furthermore, the prevalence of AR is increasing and reaches 50% in some populations. 2,3 Although AR has been studied in recent years, the details of the underlying pathogenic mechanisms remain unclear.…”
mentioning
confidence: 99%
“…1 Furthermore, the prevalence of AR is increasing and reaches 50% in some populations. 2,3 Although AR has been studied in recent years, the details of the underlying pathogenic mechanisms remain unclear.…”
mentioning
confidence: 99%
“…The prevalence of allergic diseases including allergic rhinitis (AR) largely increased not only in developed countries [1,2] but also in developing countries [3,4] in the recent decades. China, as the largest developing country, has experienced a rapid increasing in the prevalence of AR.…”
mentioning
confidence: 99%
“…Epidemiological studies have revealed that the prevalence of AR has increased progressively in the moredeveloped countries, and currently affects up to 40% of the population worldwide (12)(13)(14)(15). Likewise, rising trend of AR has also been observed globally in the past decades; with a widely varying prevalence particularly in the developing nations, including in China (16).…”
Section: Introductionmentioning
confidence: 99%